Paintball – a game leading to serious visual disorders - Bieliński, Paweł; Mackiewicz, Jerzy; Jasielska, Monika; Olejniczak, Monika (Polish Journal of Public Health, 2010)
Introduction. About 13% of all ocular traumas are sport-related injuries. Recently, there has been an increase in serious paintball-related injuries of the eye and a related loss of vision. Aim. The aim of our study was to present cases with paintball-related ocular trauma. Materiał and methods. Three patients (2 males – 17 and 46 yrs, and 1 female – 38 yrs) were admitted to the Department of Ophthalmology in Lublin in 2010. In two of the cases the injury occurred while playing paintball without the required protection gear. The third patient was a viewer who, at one point, left the safe place reserved for the spectators. The follow-up of the patients lasted from 3 weeks to 4 months. Visual acuity was very poor, ranging from CF to 0.02, and was, undoubtedly, related to a severe retinal injury. In one of the cases a retinal detachment was observed and, in two of the cases, a macular hole was diagnosed. The examination revealed vitreous hemorrhage in all the patients. In one of the cases a pars plana vitrectomy was performed. In all the cases the clinical condition improved after the treatment. However, there was little improvement in the patients’ functionality. Conclusions. A blunt trauma caused during a paintball game may lead to a serious ocular injury and a potential loss of vision. Because of the increase in the number of trauma cases occurring in paintball players, a public debate is necessary. The emerging problems are not only related to the sight-threatening injuries, but also to the participation of young people in activities which are based on direct shooting at each other.